Assessing Fraud Pentagon Theory's Impact on Financial Statement Fraud Risk in Indonesian Mining Firms - Putra, Faisal Riyanda; Respati, Novita Weningtyas; Hudaya, Muhammad (E-Jurnal Akuntansi; Vol 35 No 2 (2025)DO - 10.24843/EJA.2025.v35.i02.p10, 2025)
This study examines the applicability of the Fraud Pentagon Theory in detecting fraudulent financial reporting within the mining sector. The theory comprises five elements—hubris, pressure, opportunity, justification, and capability—which collectively offer a more comprehensive framework for understanding the motivations and conditions that facilitate financial statement fraud. The research population includes all mining companies listed on the Indonesia Stock Exchange from 2016 to 2019. Using purposive sampling, 48 companies were selected for analysis. Logistic regression was employed to evaluate the influence of Fraud Pentagon indicators on the likelihood of fraudulent financial reporting. The findings indicate that variables such as auditor changes, company characteristics, external pressure, financial stability, and the pursuit of financial targets significantly influence the risk of misleading financial disclosures. Meanwhile, factors including the frequency of CEO photographs in annual reports, changes in board directors, weak internal controls, and managerial ownership were found to have a more limited effect. These results highlight the importance of a multidimensional approach in detecting and mitigating financial reporting fraud. Stakeholders such as regulators, auditors, corporate management, and boards of commissioners should consider these indicators when assessing fraud risk to enhance transparency and safeguard the integrity of financial information. Keywords: Fraud Pentagon Theory; Potential Fraud; Pressure; Opportunity; Rationalization; Ability; Arrogance.